2009
DOI: 10.1590/s0034-71402009000200003
|View full text |Cite
|
Sign up to set email alerts
|

The natural rate of interest in Brazil between 1999 and 2005

Abstract: The aim of the present study is to estimate the level of the natural rate of interest in Brazil. First, statistical filters are used for the ex ante and ex post real interest series. Then, an estimation of a dynamic Taylor rule is performed. These two estimates are eventually compared with the natural rate of interest obtained from a simplified macroeconomic state-space model following Laubach and Williams (2003

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Barcellos Neto and Portugal (2009) estimated the neutral interest rate for Brazil by applying statistical filters on the series of ex-ante and ex-postreal interest rates and estimating a dynamic Taylor Rule (i.e. a dynamic reaction function).…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Barcellos Neto and Portugal (2009) estimated the neutral interest rate for Brazil by applying statistical filters on the series of ex-ante and ex-postreal interest rates and estimating a dynamic Taylor Rule (i.e. a dynamic reaction function).…”
Section: Review Of Literaturementioning
confidence: 99%
“…from 2005 onwards given the lack of estimates for the neutral rate from this point in time on), it was found that the neutral interest rate has been on a downward trajectory since 2006. An evaluation was also carried out on the conduct of the CB's monetary policy in recent years and, in general, the analysis showed that between the end of 2001 and 2005, the institution adopted a more conservative stance (as opposed to the result found by Barcellos Neto & Portugal, 2009) and that from then on it was closer to neutrality. Gotlieb (2013), also following Laubach and Williams (2003) and assuming a closed economy, verified a downward trend in the neutral interest rate until 2012, a dynamic particularly attributed to structural factors.…”
Section: Review Of Literaturementioning
confidence: 99%
“…With the number of EMDEs embracing inflation targeting rising-which meant that EMDEs were using interest rates to guide inflation to a predetermined target-and the popularity of estimates of the neutral interest rate such as Laubach and Williams (2003), researchers started estimating neutrals for these EMDEs. These include estimates for large EMDEs such as Brazil (de Barcellos Neto and Portugal, 2009;Duarte, 2010;Perrelli and Roache, 2014a), India (Behera et al, 2017), Mexico (Carrillo et al, 2017), and Turkey (Ögünç, 2006;Ögünç and Batmaz, 2011;Çatik and Akdeniz, 2019) and smaller ones such as Peru (Humala and Briones, 2011). Other EMDEs that have neutral estimates include Chile (Fuentes et al, 2007), Colombia (González et al, 2013), Philippines (Austria, 2018), South Africa (Kuhn et al, 2019), Thailand and Indonesia (Zhu, 2016), Kyrgyz Republic (Teodoru et al, 2020), Hungary, Poland, and Russia (Grafe et al, 2018).…”
Section: Neutral Real Interest Rate Estimates In Emdesmentioning
confidence: 99%
“… See Arida, Bacha, and Lara-Resende (2005);Barcelos-Neto and Portugal (2006); Fraga (2005);Gonçalves, Holland, and Spacov (2007);Miranda and Muinhos (2003);Muinhos and Nakane (2006); andSalles (2007).…”
mentioning
confidence: 99%